Effect of packaging method and cold-storage time on chicken meat quality. Issue 1 (2nd January 2016) - Marcinkowska-Lesiak, Monika; Zdanowska-Sąsiadek, Żaneta; Stelmasiak, Adrian; Damaziak, Krzysztof; Michalczuk, Monika; Poławska, Ewa; Wyrwisz, Jarosław; Wierzbicka, Agnieszka
Abstract : This study was performed to determine the effects of vacuum packaging (VP) and modified-atmosphere packaging (MAP) (CO2 /N2  = 3:7) on the physicochemical properties and sensory attributes in chicken breast meat during storage at 2ºC±0.5ºC for 5, 10 and 15 days. Results showed that storage time influenced the physicochemical properties, except sensory attributes, shear force and shear energy of chicken meat. The extended storage time was causing an increase in the pH value, drip loss and in values of color parameters (L, a* b*) in chicken meat. Moreover, the packaging method affected values of drip loss, cooking loss and shear force. Fresh meat (0 days of storage) was characterized by the highest overall quality assessed with the semi-consumer scaling method. Storage time and packaging method were found to exert significant effects on the physicochemical parameters determined instrumentally and on sensory attributes of meat evaluated with the semi-consumer scaling method.